PENGARUH LINGKUNGAN KERJA DAN IKLIM ORGANISASI TERHADAP SEMANGAT KERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN ASAHAN - Halimatussaddiah Halimatussaddiah; Juliwati P Batubara; Dian Wahyuni; Arinda Wiranti; Jumiarsih Jumiarsih (JURNAL PIONIR, 2020)
ABSTRACTThe background that underlies this research is an indication that the employee's work enthusiasm in theAsahan District Education Office is not optimal. There are still many constraints in carrying out tasks andemployees have not been able to work optimally. The method used in this study is a survey approach. thetype of quantitative descriptive research and the nature of the research are explanations. Data collectionmethods are by interview, questionnaire and study documentation. The population is all employees at theAsahan District Education Office, which is 77 people and determined the number of samples from the entirepopulation of 77 employees. The results of the study indicate that simultaneously there is a very significantinfluence between the Work Environment and the Organizational Climate on the Employee's Spirit at theOffice of Education Asahan Regency and partially shows that there is a significant influence between theWork Environment and Organizational Climate on the Work Enthusiasm of employees at the AsahanRegency Education Office and partially the most dominant influence on the employee's Work Enthusiasm isthe Work Environment. The conclusions of the results of the study, simultaneously and partially WorkEnvironment and Climate Climate variables significantly influence employee morale at the Asahan DistrictEducation OfficeKeywords: Work Environment, Organizational Climate, Work Spirit.